Analysis Of Grade 6 Students' Difficulties In Solving Circumference And Area Problems - Meilani, Ersha; Triananda , Shalika Fajrin; Sielvyana, Sielvyana; Komariah , Kokom (Jurnal Pendidikan Rafflesia, 2023)
The research conducted at SDN Sirnagalih Jatinangor reveals that sixth-grade students face difficulties in understanding the concept of circles, particularly circumference and area. The aim of this study is to identify the challenges students encounter when solving problems related to circumference and area of circles. The research employed a qualitative approach, with sixth-grade students from SDN Sirnagalih as the data source. The findings indicate that the students' academic performance in mathematics, specifically in the topic of circumference and area of circles, remains low, with only 5 out of 26 students achieving the set benchmark. Several factors contribute to the students' difficulties, such as a lack of attention to the taught material, slow learning pace among some students, and an unsupportive learning environment. To address these issues, it is recommended to use more effective teaching approaches utilizing visual aids and physical models, provide special attention to slow learners, involve parents in supporting learning at home, and create a conducive learning environment. These measures aim to enhance students' understanding of circle-related concepts and overcome difficulties in problem-solving.